Investigation of the potential application of sodium bentonite as an excipient in formulation of sustained release tablets - Jamal Alyoussef Alkrad; Reham Abu Shmeis; Iyad Alshwabkeh; Husam Abazid; Mohammad Amin Mohammad (Elsevier, 2017)
In this study, the application of sodium bentonite (SB) in formulation of tablets prepared by direct compression for oral administration was tested. Three different model drugs with different solubilities: paracetamol, diclofenac sodium and metformin HCl were tested. Each drug was mixed with SB at ratio of 50% and the mixtures were subsequently compressed. Compatibility studies were conducted using both Deferential Scanning Calorimeter (DSC) and Fourier Transform Infrared Spectroscopy (FTIR). The dissolution profile for each drug was determined in USP-buffers at different time intervals. Diclofenac sodium in pH 6.8 buffer and paracetamol in both pH 6.8 and pH 4.5 buffers showed extended release. However, metformin HCl showed immediate release at the different pH values. The study showed that using SB was possible to prepare tablets with different release profiles. However, these profiles differ depending on dissolution media and drug type.